1995
DOI: 10.21236/ada430616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preexisting Corrosion on Fatigue Cracking of Aluminum Alloys 2024-T3 and 7075-T6

Abstract: The public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Department of Defense, Washington Headqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A cutting edge problem is the prognosis of fatigue performance limited by the interaction of aluminium alloy static corrosion during ground‐basing and cyclic loading during flight 1–5 . Loading environment can range from salt water spray at sea‐level altitudes to very low water vapour pressures and temperatures at higher altitudes 5 .…”
Section: Introductionmentioning
confidence: 99%
“…A cutting edge problem is the prognosis of fatigue performance limited by the interaction of aluminium alloy static corrosion during ground‐basing and cyclic loading during flight 1–5 . Loading environment can range from salt water spray at sea‐level altitudes to very low water vapour pressures and temperatures at higher altitudes 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue performance of aluminum alloys deteriorates in the presence of corrosion pits (Ref [16][17][18][19][20]. Several studies observed that the presence of pre-existing corrosion pits reduces the fatigue life of aluminum alloys considerably (by a factor ranging from 10 to 100) in comparison to that without corrosion pit ( Ref 15,19,21).…”
Section: Introductionmentioning
confidence: 99%